2016
DOI: 10.3928/00485713-20160502-01
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems and Disorders in Patients with Depression

Abstract: Both sleep disorders and major depressive disorder are significant clinical and public health problems that lead to increased mortality and morbidity, as well as increased health care costs. Sleep problems and disorders are more prevalent in patients with depression. Although in some people sleep problems and disorders may start before the onset of depressive symptoms, in others they may co-occur with depressive symptoms or persist after treatment of depression. Sleep problems and disorders may also increase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…Psychiatric disorders and disordered sleep-wakefulness or circadian rhythms are frequently associated, often with bidirectional relationship as in the case of insomnia and depression [ 33 , 34 , 35 ]. Insomnia occurs in over 90% of patients with clinical depression [ 36 ] and is an established risk factor for depression (odds ratio for developing depression: 6.2) and relapsed depression in treated patients [ 37 ].…”
Section: Sleep-mental Health Interplaymentioning
confidence: 99%
“…Psychiatric disorders and disordered sleep-wakefulness or circadian rhythms are frequently associated, often with bidirectional relationship as in the case of insomnia and depression [ 33 , 34 , 35 ]. Insomnia occurs in over 90% of patients with clinical depression [ 36 ] and is an established risk factor for depression (odds ratio for developing depression: 6.2) and relapsed depression in treated patients [ 37 ].…”
Section: Sleep-mental Health Interplaymentioning
confidence: 99%
“…Patients who experience major depressive disorder or anxiety disorders often have comorbid sleep difficulties [ 7 ], and patients who complete CBT for depression and anxiety often still have elevated sleep problems after treatment [ 8 , 9 , 10 ]. Sleep problems such as insomnia have been associated with an increased risk for developing medical and psychiatric disorders [ 11 , 12 ], and a bidirectional relationship has been found between insomnia and depression [ 13 ]. In a population-based prospective study examining the relationship between insomnia and depression [ 14 ], individuals who had insomnia at baseline were at an increased risk of developing major depressive disorder (OR: 6.2), and those with major depressive disorder at baseline were at an increased risk of developing insomnia (OR: 6.7).…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia not only affects cognitive function and emotion regulation but is also strongly associated with several related neuropsychiatric disorders [ 38 ]. Depression and insomnia have a bidirectional relationship [ 39 ]. In a 40-year longitudinal follow-up study of medical students, it was found that individuals with baseline insomnia were twice as likely to develop the major depressive disorder than those who did not [ 40 ].…”
Section: Insomnia and Neuropsychiatric Disordersmentioning
confidence: 99%